2020
DOI: 10.1186/s12943-020-01221-6
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circSATB2 promotes progression of non-small cell lung cancer cells

Abstract: Background: Lung cancer has high morbidity and mortality worldwide with non-small cell lung cancer (NSCLC) accounting for 85% of the cases. Therapies for lung cancer have relatively poor outcomes and further improvements are required. Circular RNAs have been reported to participate in the occurrence and progression of cancer. Information on the functions and mechanism of circRNAs in lung cancer is limited and needs more exploration. Methods: We detected expression of genes and proteins by qPCR and western blot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
179
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(206 citation statements)
references
References 40 publications
(39 reference statements)
7
179
0
Order By: Relevance
“…25 Zhang et al found that circ_SATB2 accelerated NSCLC progression through acting as miR-326 sponge to up-regulate FSCN1 expression. 15 Here, we found that circ_SATB2 was highly expressed in NSCLC tissues and cell lines. Subsequently, we investigated if Cela suppressed NSCLC progression by reducing circ_SATB2 expression.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…25 Zhang et al found that circ_SATB2 accelerated NSCLC progression through acting as miR-326 sponge to up-regulate FSCN1 expression. 15 Here, we found that circ_SATB2 was highly expressed in NSCLC tissues and cell lines. Subsequently, we investigated if Cela suppressed NSCLC progression by reducing circ_SATB2 expression.…”
Section: Discussionmentioning
confidence: 70%
“…14 As for circRNA SATB homeobox 2 (circ_SATB2), Zhang et al demonstrated that circ_SATB2 accelerated NSCLC development. 15 However, the working mechanism of circ_SATB2 in NSCLC progression remains to be illustrated.…”
Section: Introductionmentioning
confidence: 99%
“…36 Further, recent research has demonstrated that exosomal circRNAs affect LUAD development and progression by modulating the activation of LUAD-associated molecules and pathways and may be used as LUAD markers for treatment. [22][23][24] GO and KEGG pathway analyses were used to further understand the potential role of the differentially expressed circRNAs. These genes were assessed using GO function analysis to annotate likely functions.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to improve treatments for NSCLC, new therapeutic strategies, such as the development of noncytotoxic targeted agents, have emerged [ 24 27 ]. Moreover, the targeted therapies have significantly improved clinical outcomes in a subset of lung cancer patients whose tumors harbor EGFR [ 28 ], ALK [ 29 , 30 ], and HER2 alterations [ 31 33 ].…”
Section: Introductionmentioning
confidence: 99%